Lentivirus-mediated knockdown of astrocyte elevated gene-1 inhibits growth and induces apoptosis through MAPK pathways in human retinoblastoma cells - Chang, Ying; Jonas, Jost B. (PLOS ONE, 2016)
Purpose To explore expression and function of astrocyte elevated gene-1 (AEG-1) in human retinoblastoma (RB). Methods The expression of AEG-1 in histological sections of human RBs and in RB cell lines was examined using immunohistochemical staining and RT-PCR and Western blotting respectively. We knocked down AEG-1 gene levels by AEG-1-siRNA lentivirus transfection of human RB cell lines SO-RB50 and Y79, and using an MTT assay, we assessed the role of AEG-1 on RB cell proliferation. The biological significance of lentivirus transfection induced AEG-1 down-regulation was examined by assessing the apoptosis rate in the transfected RB cells by Annexin V-APC staining and flow cytometry. We additionally measured the expression of Bcl-2, Bax, cleaved-caspase-3 and caspase-3, and the phosphorylation and non-phosphorylation alternation of MAPKs. Results AEG-1 expression was detected to be strongly positive in the histological slides of 35 out of 54 (65%) patients with RB. AEG-1 expression increased significantly (P<0.05) with tumor stage. In the RB cell lines SO-RB50, Y79 and WERI-RB1 as compared with retinal pigment epithelium cells, expression of AEG-1 mRNA and AEG-1 protein was significantly higher. In AEG-1-siRNA lentivirus transfected cell cultures as compared with negative control lentivirus transfected cell cultures, levels of AEG-1 mRNA and of AEG-1 protein (P<0.05) and cell growth rates (P<0.01) were significantly lower, and apoptosis rate (P<0.001), Bax/Bcl-2 ratio and cleaved-caspase-3 protein level were significantly increased. The P-ERK/ERK ratio was significantly decreased in the AEG-1-siRNA lentivirus transfected cell lines. Conclusions Expression of AEG-1 was associated with RB, in histological slides of patients and in cell culture experiments. Lentivirus transfection induced knockdown of AEG-1 had a tumor suppressive effect, potentially by tumor cell apoptosis induction through inhibition of ERK.
Gesehen am 25.01.2019